Cell membrane-targeting NIR fluorescent probes with large Stokes shifts for ultralong-term transplanted neural stem cell tracking - Chen, Jing; Li, Dan; Li, Hongfu; Zhu, Kongkai; Shi, Leilei; Fu, Xuemei (Frontiers in Bioengineering and Biotechnology, 2023)
There is an emerging therapeutic strategy to transplant the stem cells in diseased host tissue for various neurodegenerative diseases, owing to their ability to self-renew and pluripotency. However, how to trace the transplanted cells long time limits the further understanding the mechanism of the therapy. Herein, we designed, synthesized a quinoxalinone scaffold-based NIR fluorescent probe named as QSN, which exhibits ultra-strong photostability, large Stokes shift and cell membrane-targeting capacity. It could be found that QSN labeled human embryonic stem cells showed strong fluorescent emission and photostability both in vitro and in vivo. Additionally, QSN would not impair the pluripotency of embryonic stem cells, indicating that QSN did not perform cytotoxicity. Moreover, it is worth mentioning that QSN labeled human neural stem cells held cellular retention at least 6 weeks in mouse brain striatum post-transplantation. All these findings highlight the potential application of QSN for ultralong-term transplanted cells tracking.